2021
DOI: 10.1016/j.jiph.2020.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The immediate psychological response of the general population in Saudi Arabia during COVID-19 pandemic: A cross-sectional study

Abstract: Background The outbreak of COVID-19 may differentially exacerbate anxiety and stress in people subjected to the real or perceived threat of the virus. Method An online cross-sectional survey was carried out to assess the general population’s psychological response during the initial state of the outbreak in Saudi Arabia. The study used brief screening tools PHQ-4 for anxiety-depression symptoms and IES-6 for posttraumatic stress disorder symptoms. Results… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…Nearly one year passed since the onset of COVID-19, the prevalence of psychological distress among parents in our study was 21.2%, in which only 3.3% were moderate to severe symptom. Using the cut-off point of 6 in PHQ-4, our result was greatly lower than the prevalence of moderate to severe symptom in Germany and Austria (19.0%) ( Schnell and Krampe, 2020 ), America (11.2%-11.3%) ( Kämpfen et al, 2020 ; Pan et al, 2021 ), and Saudi Arabia (14.5%) ( Joseph et al, 2021 ). In addition to the disparities of the cultural, social, and economic backgrounds, the environment people live may also play an essential role in stabilizing their emotions.…”
Section: Discussioncontrasting
confidence: 59%
“…Nearly one year passed since the onset of COVID-19, the prevalence of psychological distress among parents in our study was 21.2%, in which only 3.3% were moderate to severe symptom. Using the cut-off point of 6 in PHQ-4, our result was greatly lower than the prevalence of moderate to severe symptom in Germany and Austria (19.0%) ( Schnell and Krampe, 2020 ), America (11.2%-11.3%) ( Kämpfen et al, 2020 ; Pan et al, 2021 ), and Saudi Arabia (14.5%) ( Joseph et al, 2021 ). In addition to the disparities of the cultural, social, and economic backgrounds, the environment people live may also play an essential role in stabilizing their emotions.…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, the current study highlighted that about 14.4% of participants reported moderate to severe symptoms. This prevalence rate was comparable with the rate reported in Germany and Austria 21 (19%), America 22 (11.2%), and Saudi Arabia 23 (14.5%), but a much lower rate was recorded in China 10 (3.3%). The varying degrees of reported psychological distress across different countries are likely due to the demographic differences and cultural differences between the study populations.…”
Section: Discussionsupporting
confidence: 85%
“…A sample study on psychological impact on the general population in the context of Saudi Arabia was carried out at the time of COVID-19 curfew and lockdown, and revealed that stress, anxiety, and depression were majorly found in medical workers, students, females, and persons with a mental disorder, and 1/4th of the sample population experienced moderate to serious psychological effects [ 24 , 25 ]. Another sample study for Saudi Arabia during the first wave of Corona virus disease stated that a marginal but substantial portion of the general population had found symptoms of anxiety and depression, and a majority of them reported symptoms of psychological distress [ 26 ]. The emotional wellbeing in any society is defined by measuring distress, depression, anxiety, and behavioral control among the people.…”
Section: Review Of Literaturementioning
confidence: 99%